Evolution Model for the Absheron Mud Volcano: From In Situ Observations to Numerical Modeling. Issue 3 (19th March 2019) - Blouin, Arthur; Imbert, Patrice; Sultan, Nabil; Callot, Jean‐Paul
Abstract: The morphology of mud volcanoes (MVs) has been extensively studied over the last few decades. Although recent research has begun to focus on deep processes and structures, little is known about mud generation mechanisms. This study aims to investigate the feeder system and formation of an active kilometer‐scale MV by relying on a 3‐D seismic survey and an in situ data set on the Absheron anticline (South Caspian Basin). Seismic data show a depleted area in the Anhydritic Surakhany Formation (ASF), whose mineralogical composition fits with surface mud. Well data show that the ASF is a succession of evaporitic beds and low‐temperature shales near its fracture pressure. Biostratigraphic analysis confirms a Pliocene origin for the mud, suggesting that the ASF may be the source. Numerical modeling of sedimentation coupled with laboratory test results and well sonic logs fairly reproduces the observed in situ overpressure trend. Two‐dimensional methane diffusion coupled with overpressure caused by rapid sedimentation highlights the superposition of critical fracturing conditions with methane‐saturated sediments at the base of the studied MV. The present study demonstrates the predominant role of fluid overpressure due to sedimentation and gas saturation in the formation of the Absheron MV, and this is shown to occur as follows: (1) methane migration through the thrust‐related faults reaching the ASF, accompanied by (2) lateral overpressure, caused by rapid sedimentation, diffusing along the ASF leading to (3) hydro‐fracturing of overpressured and methane‐saturated sediments resulting in an important decrease in overpressure, causing (4) gas exsolution and expansion triggering sediment remobilization. Plain Language Summary: Mud volcanoes have proved to be a real risk for people living near them (e.g., Lusi catastrophe, Indonesia) and for infrastructures. While their surface morphology is well understood and their plumbing system is correctly imaged by high‐resolution seismic technology, their formation mechanisms and their trigger is yet to be understood. The South Caspian Basin is known for the presence of a large number of active structures. On the Absheron anticline, a giant active mud volcano is surrounded and covered by a large data set from seismic imaging to sediment cores. From the analysis of the seismic data, and from diverse measurements on sediments, we were able to locate the source of the mud, which is shallower than the source for many mud volcanoes in the region. We developed a numerical model able to reproduce the pore pressure trends recorded at the wells, and it shows that the interaction between methane‐saturated areas and potential rupture zones is able to explain the mud volcano location. Finally, based on the different results and observations, a formation model is proposed where hydrofracturing is the initial trigger for the subsequent gas exsolution and expansion that disaggregate and remobilize weak sedimentary layers. Key Points: The Absheron mud volcano, unlike many mud volcanoes in the South Caspian Basin, is not sourced from the deep Maykop Formation but from the Upper Productive Series The developed numerical model shows that an interaction between methane‐saturated areas and potential rupture zones allows locating the mud volcano formation A formation model is proposed where hydrofracturing is the initial trigger for the subsequent gas exsolution and expansion that disaggregate and remobilize weak sedimentary layers